p19Arf sensitizes B16 melanoma cells to interferon-β delivered via mesenchymal stem cells in vitro - R.C. Da-Costa; I.L. Vieira; A. Hunger; R.E. Tamura; B.E. Strauss (Brazilian Journal of Medical and Biological Research, 2020)
The immune stimulatory and anti-neoplastic functions of type I interferon have long been applied for the treatment of melanoma. However, the systemic application of high levels of this recombinant protein is often met with toxicity. An approach that provides localized, yet transient, production of type I interferon may overcome this limitation. We propose that the use of mesenchymal stem cells (MSCs) as delivery vehicles for the production of interferon-β (IFNβ) may be beneficial when applied together with our cancer gene therapy approach. In our previous studies, we have shown that adenovirus-mediated gene therapy with IFNβ was especially effective in combination with p19Arf gene transfer, resulting in immunogenic cell death. Here we showed that MSCs derived from mouse adipose tissue were susceptible to transduction with adenovirus, expressed the transgene reliably, and yet were not especially sensitive to IFNβ production. MSCs used to produce IFNβ inhibited B16 mouse melanoma cells in a co-culture assay. Moreover, the presence of p19Arf in the B16 cells sensitizes them to the IFNβ produced by the MSCs. These data represent a critical demonstration of the use of MSCs as carriers of adenovirus encoding IFNβ and applied as an anti-cancer strategy in combination with p19Arf gene therapy.